Rancang Bangun Turbin Propeller Open Flume Head Rendah Dengan Enam Sudu - Daru Sugati (Retii, 2022)
The design of the low-flume head open-flume turbine with six blades is designed and built based on the potential of Indonesia's remote areas which have adequate water flow to build power plants to meet the energy needs of rural communities and the manufacturing process is easy. When other energy sources start to run low and have a negative impact, water can be used as energy that can be used as an energy source for electricity generation that is cheap and does not cause pollution. The purpose of this research is to manufacture energy-efficient micro-hydro power plants (PLTMH) which are included in renewable energy, determine turbine power and efficiency by testing flow variations. The research method was carried out experimentally with an open flume propeller turbine with the parameters of the number of blades 6 blades, at a head of 2 meters and variations in the discharge of 160 Lpm, 180 Lpm, and 200 Lpm. Arduino Mega and load cel and tachometer sensors are used to take torque and rotation data. The flow rate data is taken using a zj-lcd-m flowmeter. After data retrieval is then processed to obtain power and efficiency, then graphs are made of the influence of rotation on torque, the effect of rotation on power, the effect of rotation on efficiency, the ratio of torque and power at 160 Lpm discharge, torque and power ratio at 180 Lpm discharge, torque and power ratio at a discharge of 180 Lpm, a comparison of efficiency and head at a discharge of 160, a comparison of efficiency and head at a discharge of 180, a comparison of efficiency and head at a discharge of 200. The results showed that the process of making a micro hydro power plant (PLTMH) can be done easily, the type of turbine used is a propeller turbine, the number of blades is six blades with a diameter of 0.11 m, a shaft neck diameter of 0.04 m and a head of 2 m, with discharge variations of 160 Lpm, 180 Lpm, and 200 Lpm. Best power 1.5 watt, 2.8 watt, 3.4 watt. Best turbine efficiency 2.88%, 4.77%, 5.20%